2015
DOI: 10.1177/0886260515596334
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Violence in the Context of Drug Use Among Young Adult Opioid Users in New York City

Abstract: Drug and alcohol use have been associated with increased risk for sexual violence, but there is little research on sexual violence within the context of drug use among young adult opioid users. The current mixed-methods study explores young adult opioid users’ sexual experiences in the context of their drug use. Forty-six New York City young adults (ages 18–32) who reported lifetime nonmedical use of prescription opioids (POs) completed in-depth, semistructured interviews, and 164 (ages 18–29) who reported her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…Emerging research among young adults has pointed to prescription opioid misuse as a potential risk factor for SV victimization, as the victim may be incapacitated at the time of victimization or exchanging drugs for sex which increases SV risk [21]. For TDV, Parker et al used cross-sectional latent class analysis (LCA) to classify adolescents based on their alcohol, tobacco, marijuana, and prescription drug use [13].…”
mentioning
confidence: 99%
“…Emerging research among young adults has pointed to prescription opioid misuse as a potential risk factor for SV victimization, as the victim may be incapacitated at the time of victimization or exchanging drugs for sex which increases SV risk [21]. For TDV, Parker et al used cross-sectional latent class analysis (LCA) to classify adolescents based on their alcohol, tobacco, marijuana, and prescription drug use [13].…”
mentioning
confidence: 99%
“…The different time periods covered by sexual and drug use variables limit the conclusions that can be reached from their associations. In addition, an earlier paper by this project reported that some men have sex with women or MSM opioid users when they are semi-conscious or unconscious due to the effects of drugs (30). This could lead to under-reporting of partnerships and other sexual risks by these unwitting partners.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual victimization history, another HIV transmission risk factor, was also associated with alternate routes of administration. These risk factors may be exacerbated when combined with other behaviors associated with prescription opioid misuse, including risky injection practices and sex while high (Mateu-Gelabert et al 2015, Jessell et al 2015, Meade et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…The misuse of prescription opioids among young people is associated with several health and social problems, including mental distress, victimization, and homelessness (Schrager et al 2014, Mackesy-Amiti, Donenberg, and Ouellet 2015, Jessell et al 2015). The use of alternate routes of administration of prescription opioids, including snorting, smoking, or injecting, may result in increased vulnerability, as the effects of the drug are intensified and the risk of addiction is elevated (Compton and Volkow 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation